2011
DOI: 10.1111/j.1744-7429.2011.00835.x
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Island Rule’ Acting on Anuran Populations (Bufonidae: Rhinella ornata) of the Southern Hemisphere

Abstract: Darwin and Wallace, in the mid-nineteenth century, were the first to document examples of natural selection acting on island dwellers. A century later a pattern of morphological differences among organisms on islands was coined the 'island rule', which states that on islands species with small individuals tend toward gigantism and large individuals tend toward dwarfism. Selective pressures such as limited resources and increased intraspecific competition modulate the size of organisms in these environments. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 30 publications
3
21
1
Order By: Relevance
“…However, exceptions occur, such as Rhinella ornata (Spix, 1824) (larger on the mainland) in Rio de Janeiro, Brazil (MONTESINOS et al 2012). This difference between dwarfism and gigantism on islands and continents is probably due to the complex interaction between food, space and predation (WU et al 2006), but may also be explained by the size range of the animals in question.…”
Section: Discussionmentioning
confidence: 99%
“…However, exceptions occur, such as Rhinella ornata (Spix, 1824) (larger on the mainland) in Rio de Janeiro, Brazil (MONTESINOS et al 2012). This difference between dwarfism and gigantism on islands and continents is probably due to the complex interaction between food, space and predation (WU et al 2006), but may also be explained by the size range of the animals in question.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from studies on the island rule that focus on mammals (e.g. Bromham & Cardillo, ; Lyras, Van Der Geer, & Rook, ; Meiri, Dayan, & Simberloff, ; Palombo, ; Rozzi & Palombo, ), researchers have also applied and tested this general hypothesis for a number of other taxonomic groups, including amphibians (Montesinos, Silva, & Carvalho, ), birds (e.g. Boyer & Jetz, ; Clegg & Owens, ), dinosaurs (Benton et al., ), fish (Herczeg, Gonda, & Merilä, ), insects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies, however, report changes in body size for single species or populations and then relate their observations to the island rule. Examples are found across taxa: insects (Hoch et al, 2014;Pizzo, Mazzone, Rolando, & Palestrini, 2011), fishes (Herczeg et al, 2009), amphibians (Montesinos et al, 2012), dinosaurs (e.g. Benton et al, 2010), birds (Mathys & Lockwood, 2009), and a number of mammalian species including mice (Michaux, de Bellocq, Sar a, & Morand, 2002), deer (Simard, Côt e, Weladji, & Huot, 2008) and marten (L opez-Mart ın, Ruiz-Olmo, & Padr o, 2006).…”
mentioning
confidence: 99%
“…On the other hand, specimens of A. marmoratafrom Alcatrazes Island (CCS J) are much larger than specimens from other populations (male minimum SVL 25.6 mm, n = 1, female minimum SVL 25.7 mm, n = 4; other mainland populations male maximum SVL 22.4, n = 37, female maximum SVL = 23.4 mm, n = 24). Vertebrate gigantism on islands has massively been reported in the literature ( [78][79][80]). Nevertheless, Rebouças et al [80] found opposite results, (i.e.…”
Section: Variation In a Widespread Species In The Atlantic Forestmentioning
confidence: 99%